2018
DOI: 10.1152/jn.00609.2018
|View full text |Cite
|
Sign up to set email alerts
|

Maximal strength training: the impact of eccentric overload

Abstract: The search for the most potent strength training intervention is continuous. Maximal strength training (MST) yields large improvements in force-generating capacity (FGC), largely attributed to efferent neural drive enhancement. However, it remains elusive whether eccentric overload, before the concentric phase, may augment training-induced neuromuscular adaptations. A total of 53 23 ± 3 (SD)-yr-old untrained males were randomized to either a nontraining control group (CG) or one of two training groups performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
2
25
0
2
Order By: Relevance
“…In fact, in studies comparing solely concentric low intensity (75% of 1RM) contractions with concentric and subsequent eccentric overload contractions (> 100% of 1RM), superior 1RM gains are reported from subsequent eccentric overload [47,48]. While studies comparing solely concentric higher intensity (maximal 6-and 10RM and > 85% of 1RM) with subsequent eccentric overload reported similar gains in 1RM [49,50]. This may suggest that as long as the concentric phase is performed with heavy loads (~≥ 85% of 1RM), no extra maximal strength gains can be derived from additional eccentric overload [24].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in studies comparing solely concentric low intensity (75% of 1RM) contractions with concentric and subsequent eccentric overload contractions (> 100% of 1RM), superior 1RM gains are reported from subsequent eccentric overload [47,48]. While studies comparing solely concentric higher intensity (maximal 6-and 10RM and > 85% of 1RM) with subsequent eccentric overload reported similar gains in 1RM [49,50]. This may suggest that as long as the concentric phase is performed with heavy loads (~≥ 85% of 1RM), no extra maximal strength gains can be derived from additional eccentric overload [24].…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration specific to training status is the relative strength levels of the individuals. While several studies provide some measure of the participants' maximal absolute strength [94,95,97,110,111], a paucity of research provides relative strength measurements [112]. It should be noted that stronger individuals may require greater CON velocities or use larger inertial loads while using flywheel devise to experience an ECC overload stimulus.…”
Section: Flywheel Inertial Trainingmentioning
confidence: 99%
“…When interpreting the findings of the comparative FIT literature, it is important to consider the quality of the prescribed training programs. For example, a number of existing training studies compared training with the flywheel device with weight stack machine training [93,95,110,113] while other studies compared FIT to a control condition that included no additional training [98,111]. The previous studies comparing flywheel and weight stack machine training indicated that greater results were produced with the flywheel device; however, it should be noted that the majority of the training Something to consider when interpreting the results of the existing FIT studies is the training status of the individuals being tested.…”
Section: Flywheel Inertial Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…While it appears that four sets of seven repetitions may be an effective FIT protocol for hypertrophy, strength, and power output, limited information exists on whether this is optimal for all populations. To the authors' knowledge, only one study has provided information regarding the relative strength of their participants [44], despite several others providing measures of absolute strength [31,34,41,48,57]. From a strength perspective, stronger athletes require a greater overload stimulus than weaker athletes due to their capacity to tolerate heavier loads.…”
Section: Flywheel Inertial Trainingmentioning
confidence: 99%